Functional Role of the Cerebellum in Parkinson Disease: A PET Study. (8th June 2021) - Riou, Audrey; Houvenaghel, Jean-François; Dondaine, Thibaut; Drapier, Sophie; Sauleau, Paul; Drapier, Dominique; Duprez, Joan; Guillery, Murielle; Le Jeune, Florence; Verin, Marc; Robert, Gabriel
Abstract : Objectives: To test for cerebellar involvement in motor and nonmotor impairments in Parkinson disease (PD) and to determine patterns of metabolic correlations with supratentorial brain structures, we correlated clinical motor, cognitive, and psychiatric scales with cerebellar metabolism. Methods: We included 90 patients with PD. Motor, cognitive, and psychiatric domains were assessed, and resting-state 18 FDG-PET metabolic imaging was performed. The motor, cognitive, and psychiatric scores were entered separately into a principal component analysis. We looked for correlations between these 3 principal components and cerebellar metabolism. Furthermore, we extracted the mean glucose metabolism value for each significant cerebellar cluster and looked for patterns of cerebrum-cerebellum metabolic correlations. Results: Severity of impairment was correlated with increased metabolism in the anterior lobes and vermis (motor domain); the right crus I, crus II, and declive (cognitive domain); and the right crus I and crus II (psychiatric domain). No results survived multiple testing corrections regarding the psychiatric domain. Moreover, we found distributed and overlapping, but not identical, patterns of metabolic correlations for motor and cognitive domains. Specific supratentorial structures (cortical structures, basal ganglia, and thalamus) were strongly correlated with each of the cerebellar clusters. Conclusions: These results confirm the role of the cerebellum in nonmotor domains of PD, with differential but overlapping patterns of metabolic correlations suggesting the involvement of cerebello-thalamo-striatal-cortical loops.